Profil Gelatinisasi dan Sifat Fisik Tepung Campolay Masak Penuh dan Lewat Matang (Pouteria campechina) Gelatinization Profiles and Physical Propertis of Ripe and Over Ripe Canistal Flour (Pouteria campechiana) - Nursyawal Nacing; Ari Irawan; Sri Rejeki Retna Pertiwi; Aminullah Aminullah (JURNAL AGROINDUSTRI HALAL, 2021)
This research aims to study gelatinization profile and physical properties of ripe and overripe canistel flour. Data statistically analyzed using the independent sample T-tes. Analyzed of the chemical properties of canistel fruits include water content, starch content, and sugar content, while analyzed canistel flour includes gelatinization profile, shape and size of starch granules with color test. The results of the analyzed showed that the water content and sugar content of ripe canistel fruit is higher than those of overripe canistel fruit, while the lower starch content. The total starch and amylose content of ripe canistel flour is higher than that of overripe flour. Analyzed the results of gelatinization profile ripe canistel flour has a peak viscosity, final viscosity, and  higher gelatinization temperature than the finished canistel flour and the gelatinization faster time. Analysis of the physical properties of the color parameters of canistel flour produces the reddish yellow color, while of the shape and size of the canistel flour starch granule shape that are round with size ranges between 2-7 µm.Keywords: Canistel fruit, canistel flour, gelatization profile.